Further understanding the connection between Alzheimer's disease and Down syndrome. Issue 7 (16th June 2020) - Snyder, Heather M.; Bain, Lisa J.; Brickman, Adam M.; Carrillo, Maria C.; Esbensen, Anna J.; Espinosa, Joaquin M.; Fernandez, Fabian; Fortea, Juan; Hartley, Sigan L.; Head, Elizabeth; Hendrix, James; Kishnani, Priya S.; et al.
Abstract: Improved medical care of individuals with Down syndrome (DS) has led to an increase in life expectancy to over the age of 60 years. In conjunction, there has been an increase in age‐related co‐occurring conditions including Alzheimer's disease (AD). Understanding the factors that underlie symptom and age of clinical presentation of dementia in people with DS may provide insights into the mechanisms of sporadic and DS‐associated AD (DS‐AD). In March 2019, the Alzheimer's Association, Global Down Syndrome Foundation and the LuMind IDSC Foundation partnered to convene a workshop to explore the state of the research on the intersection of AD and DS research; to identify research gaps and unmet needs; and to consider how best to advance the field. This article provides a summary of discussions, including noting areas of emerging science and discovery, considerations for future studies, and identifying open gaps in our understanding for future focus.